Measurement of the t t ¯ H $$ t\overline{t}H $$ and tH production rates in the H → b b ¯ $$ b\overline{b} $$ decay channel using proton-proton collision data at s $$ \sqrt{s} $$ = 13 TeV - The CMS collaboration; A. Hayrapetyan; A. Tumasyan; W. Adam; J. W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; P. S. Hussain; M. Jeitler; N. Krammer; et al. (Journal of High Energy Physics)
Abstract An analysis of the production of a Higgs boson (H) in association with a top quark-antiquark pair ( t t ¯ H $$ t\overline{t}H $$ ) or a single top quark (tH) is presented. The Higgs boson decay into a bottom quark-antiquark pair (H → b b ¯ $$ b\overline{b} $$ ) is targeted, and three different final states of the top quark decays are considered, defined by the number of leptons (electrons or muons) in the event. The analysis utilises proton-proton collision data collected at the CERN LHC with the CMS experiment at s $$ \sqrt{s} $$ = 13 TeV in 2016–2018, which correspond to an integrated luminosity of 138 fb −1. The observed t t ¯ H $$ t\overline{t}H $$ production rate relative to the standard model expectation is 0.33 ± 0.26 = 0.33 ± 0.17(stat) ± 0.21(syst). Additionally, the t t ¯ H $$ t\overline{t}H $$ production rate is determined in intervals of Higgs boson transverse momentum. An upper limit at 95% confidence level is set on the tH production rate of 14.6 times the standard model prediction, with an expectation of 19.3 − 6.0 + 9.2 $$ {19.3}_{-6.0}^{+9.2} $$ . Finally, constraints are derived on the strength and structure of the coupling between the Higgs boson and the top quark from simultaneous extraction of the t t ¯ H $$ t\overline{t}H $$ and tH production rates, and the results are combined with those obtained in other Higgs boson decay channels.